Property entrepreneur : the wealth dragon way to build a successful property business - Wong, Vincent (Wiley, 2016)
"Property Investing the Wealth Dragon Way Property Entrepreneur explains how anyone can make money from property, regardless of their financial situation. Author Vincent Wong is one of the UK's most dynamic and respected property entrepreneurs, and this book outlines his approach to creating wealth through property investing for both seasoned and aspiring investors. Emphasising the importance of treating property investing as a business, the author shares the wisdom of his first-hand experience and his investment techniques to help you navigate the ever-shifting property market and become a true property entrepreneur. There is more than one way to break into the property game, and it doesn't have to involve saving for one large deposit after another; this book covers tried and tested strategies beyond the traditional approaches to property investing. Whether you're contemplating your first, fifth or fifteenth property, Property Entrepreneur will help to light your entrepreneurial spark and show you how to turn property into profit. Property entrepreneurship is like any other business: if you want to succeed, you must take the time to learn from those who have mastered the best techniques. This book gives you access to the mind, motivations and methods of a top investor to help you start and build your own property business. This book will show you: How to start viewing property investing as a business Why you need to eliminate unproductive habits and attitudes The best ways to maximise profits and create a secure, passive income How to nurture your entrepreneurial spirit and watch your business grow Property investing can look daunting and complex to those without experience. The rules are constantly being rewritten, the goalposts are regularly shifted and the market looks like an unpredictable beast. Property Entrepreneur will challenge your preconceptions, and help you navigate the path to real, lasting wealth"--